Elliptic Equations in Weighted Sobolev Spaces on Unbounded Domains. (25th August 2008) - Boccia, Serena; Monsurrò, Sara; Transirico, Maria
Abstract : We study in this paper a class of second-order linear elliptic equations in weighted Sobolev spaces on unbounded domains ofℝ n, n ≥ 3 . We obtain an a priori bound, and a regularity result from which we deduce a uniqueness theorem.